Advanced Learning Techniques In Badminton At The Cahaya Muda Badminton Association - J, Ari Setiawan; Welis, Wilda; Chaeroni, Ahmad; Zulbahri, Zulbahri (STKIP Singkawang, 2025)
The research problem is the low smashing ability of badminton athletes at PB Cahaya Muda. Low smash accuracy is influenced by several factors, such as leg muscle explosiveness, hand-eye coordination, and arm muscle explosiveness. This study aims to reveal the direct and indirect effects, as well as the simultaneous effects between variables.This study is a quantitative associative study using a path analysis approach. The population in this study was all 55 badminton athletes at PB Cahaya Muda. The sample was taken using purposive sampling of 20 individuals. The data instruments were leg muscle explosiveness, vertical jump, hand-eye coordination using a hand-eye coordination test, arm muscle explosiveness using a one-hand medicine ball, and badminton smash accuracy. The data were analyzed using path analysis through structural model testing at α = 0.05.The results of the hypothesis testing show: (1) there is a direct influence of leg muscle explosive power on the accuracy of badminton smashes (py1 = 0.435 or 18.92%), (2) there is a direct influence of hand eye coordination on the accuracy of badminton smashes (py2 = 0.057 or 0.27%), (3) there is a direct influence of arm muscle explosive power on the accuracy of badminton smashes (py3 = 0.564 or 31.08%), (4) there is an indirect influence of arm muscle explosive power on the accuracy of badminton smashes (p31.py3 = 0.886 or 78.49%), (5) there is an indirect influence of hand eye coordination on the accuracy of badminton smashes (p32.py3 = 0.0345 total influence 3.49%), and (6) there is an influence of leg muscle explosive power, hand eye coordination and arm muscle explosive power simultaneously on the accuracy of badminton smashes (Rsquare = 0.886 or 88.6%)